Howard Jacobson - Brauner, David, 1968- (Contemporary British novelists., 2020)
This is a comprehensive and definitive study of the Man Booker Prize-winning novelist, Howard Jacobson. It offers lucid, detailed and nuanced readings of each of Jacobson's novels, and makes a powerful case for the importance of his work in the landscape of contemporary fiction.